2018
DOI: 10.1101/247031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing False Positives in CRISPR/Cas9 Screens from Copy Number Variations

Abstract: CRISPR/Cas9 knockout screens have been widely used to interrogate gene functions across a wide range of cell systems. However, the screening outcome is biased in amplified genomic regions, due to the ability of the Cas9 nuclease to induce multiple double-stranded breaks and strong DNA damage responses at these regions. We developed algorithms to correct biases associated with copy number variations (CNV), even when the CNV profiles are unknown. We demonstrated that our methods effectively reduced false positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Because of this, we believe that the most promising area for future research is in identifying issues specific to the experimental design of CRISPR-pooled screens. The recent work in identifying biases such as copy number-associated effects [30][31][32], structural rearrangement effects [33], and bottleneck effects [57] is exemplary of promising directions. We believe that there are further questions to be answered: for example, Are such biases generalizable to CRISPR interference and CRISPR activation screens?…”
Section: Recommendations For Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, we believe that the most promising area for future research is in identifying issues specific to the experimental design of CRISPR-pooled screens. The recent work in identifying biases such as copy number-associated effects [30][31][32], structural rearrangement effects [33], and bottleneck effects [57] is exemplary of promising directions. We believe that there are further questions to be answered: for example, Are such biases generalizable to CRISPR interference and CRISPR activation screens?…”
Section: Recommendations For Experimental Designmentioning
confidence: 99%
“…Varying gene effect sizes can result in a bias towards finding only genes with large effects [29]. Cell death from excessive cutting in high copy number regions can lead to false positives in CRISPRko screens [30][31][32][33]. These issues complicate the data analysis and often cause both false positives and false negatives.…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving parallel screens are straightforward to design, but technical variation in how the screens are performed as well as copy number variation across cell backgrounds can confound the results (Zhang & Lu, ; Aguirre et al , ). Recent work has shown that copy number variation can underlie the strongest hits in CRISPR‐knockout screens, and multiple groups have proposed corrective algorithms to confront this problem (Pommier, ; Meyers et al , ; Data ref: Meyers et al , ; preprint: Wu et al , ). Additional heuristics aimed at increasing the quality of genetic interactions identified from parallel genetic screens have included discarding entire screens with noisy effect sizes, setting an effect size threshold for correlating genes, and capping the number of interactions per gene (Wang et al , ; preprint: Kim et al , ; Pan et al , ); however, reliance on these heuristics prevents truly unbiased genome‐wide analyses (McFarland et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving parallel screens are straightforward to design, but technical variation in how the screens are performed as well as copy number variation across cell backgrounds can confound the results (Zhang & Lu, 2009;Aguirre et al, 2016). Recent work has shown that copy number variation can underlie the strongest hits in CRISPR knockout screens, and multiple groups have proposed corrective algorithms to confront this problem (Pommier, 2006;Meyers et al, 2017;Wu et al). Additional heuristics aimed at increasing the quality of genetic interactions identified from parallel genetic screens have included discarding entire screens with noisy effect sizes, setting an effect size threshold for correlating genes, and capping the number of interactions per gene Pan et al, 2018;Kim et al, 2018); however, reliance on these heuristics prevents truly unbiased genome-wide analyses.…”
Section: Introductionmentioning
confidence: 99%